Can gender of source make a difference in reducing sexism? An intervention study with university students - Düven Kaan, Ayşenur Dilara (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: The limited number of studies on interventions on sexism has demonstrated that reducing men’s sexism levels can be more challenging than women’s. In the current study, an attempt was made to increase the effectiveness of a brief educational intervention in a form of an essay on sexism particularly on men through manipulation of the gender of researcher. essay. It was hypothesized that compared to women, men would be more affected by the intervention, if they were informed that research on sexism was conducted by a man. 145 female and 78 male undergraduate student participants were randomly distributed on an online platform to one of the four study conditionss: intervention essay with a female researcher, intervention essay with a male researcher, control essay with a female researcher, and control essay with a male researcher. The findings of the study revealed that researcher gender and essay type did not have a significant effect on either female and male participants’ benevolent sexism scores. Women had significantly lower levels of benevolent and hostile sexism scores than men. Implications of these findings, limitations of the study and suggestions for future research are discussed.

ÖZET: Cinsiyetçilik üzerine yapılmış kısıtlı sayıdaki müdahale çalışmaları erkeklerin cinsiyetçilik seviyelerinin düşürülmesinin kadınlara göre daha zor olduğunu göstermiştir. Bu çalışmada, cinsiyetçilik üzerine bir metinden oluşan kısa bir eğitsel müdahalenin özellikle erkekler üzerindeki etkinliği, araştırmacı cinsiyetinin manipülasyonu ile artırılmaya çalışılmıştır. Erkeklerin cinsiyetçilik üzerine araştırmanın bir erkek tarafından yapıldığı yönünde bilgilendirildiklerinde, müdahaleden daha fazla etkileneceği varsayılmıştır. 145 kadın ve 78 erkek lisans öğrencisi katılımcı dört araştırma grubundan birine çevrimiçi bir platformda rastlantısal bir şekilde dağıtılmıştır: Kadın araştırmacı içeren müdahale metni, erkek araştırmacı içeren müdahale metni, kadın araştırmacı içeren kontrol metni, erkek araştırmacı içeren kontrol metni. Araştırmanın bulguları araştırmacı cinsiyetinin ve makale türünün kadın ve erkek katılımcıların iyicil cinsiyetçilik seviyeleri üzerinde anlamlı herhangi bir etkisinin olmadığını göstermiştir. Kadınların erkeklerden anlamlı düzeyde daha düşük düşmanca ve iyicil cinsiyetçilik skorlarına sahip oldukları gözlemlenmiştir. Bu bulguların anlamları ve araştırmanın sınırlılıkları ve bundan sonra yapılacak araştırmalar için öneriler tartışılmıştır.
Cinsiyetçiliğin azaltılmasında kaynağın cinsiyeti bir fark yaratabilir mi? Üniversite öğrencileriyle bir müdahale çalışması
Keywords: sexism; gender; intervention; benevolent sexism; hostile sexism; cinsiyetçilik; toplumsal cinsiyet; müdahale; iyicil cinsiyetçilik; düşmanca cinsiyetçilik